PENDIDIKAN MULTIKULTURAL DALAM PENDIDIKAN ISLAM - Sopiah * (IAIN Pekalongan, 2009)
ï»¿The paradigm of multiculturalism becomes an the idea that is contextual enough with contemporary society today. The fundamental principles of equality, fairness, openness, recognition of difference are the principle of human values that are needed in the crush of global culture. Therefore, as a cultural movement, multiculturalism is an integral part in various cultural systems in society, for the case in education is through multicultural education. Multicultural education can be implemented in Indonesia in the form of formal, informal and non formal education by integrating multicultural values in curriculum materials, through strategies, approaches and methods of learning, learning interaction as well as the early internalization of multicultural values to students. Thus education (Islam) in Indonesia will produce nation cadres that are more tolerant, inclusive and rahmatan lil alamin.